Influence of Paternalistic Leadership Style on Innovation Performance Based on the Research Perspective of the Mediating Effect of the Constructive Deviance of Employees - Li, Lin; Wang, Shiqian (Frontiers in Psychology, 2021)
This study takes the high-tech enterprise and manufacturing companies in the Yangtze River Delta as the research object, analyzed the influence of paternalistic leadership on the innovation performance of employees, and analyzed the mediating role of employees’ constructive deviance. The empirical results showed that parental leadership style of benevolent and moral leadership has a positive impact on innovation performance through employees’ constructive deviance, while authoritarian leadership has a negative impact on innovation performance by affecting employees’ constructive deviance. In practice, leaders should recognize that constructive deviance is a double-edged sword, and offer guidance to employees engage in constructive deviant behavior reasonably, leaders can create sound organizational environments to foster innovation, eliminate barriers to creativity, exert the positive impact of employees’ constructive deviance and further enhance their innovation performance.